Worldmaking at the End of History: The Gulf Crisis of 1990–91 and International Law. Issue 2 (April 2023) - Aber, Samuel L.
Abstract: This Article argues that the Gulf Crisis of 1990–91, the first major international crisis of the post-Cold War era, was a constitutive moment for international law. The Article examines the contests in the United Nations over the meaning of the Crisis and shows that these contests were also over the meaning of cooperation under international law in the "new world order." The Article casts the Gulf Crisis itself as a moment of "worldmaking, " in which the United States refashioned foundational concepts like interdependence, sovereignty, and humanity in warfare and deployed them to suit a state-centered vision of international cooperation under hierarchy.